Sistem Pendukung Keputusan Pemilihan Skuad Utama Tim Bola Voli Menggunakan Metode AHP-TOPSIS - Hangga Eka Febrianto; Muhammad Tanzil Furqon; Sigit Adinugroho (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Exercise is one of the physical activities that a person does to maintain and mprove the quality of health. One of the most widely played sports is volleyball. Brawijaya University, which is one of the major universities in Malang, currently also has several volleyball teams organized by UB Volleyball Activity Unit (UABV-UB). In every year UABV-UB always receives new member registration for students who want to join. Seeing the development and the amount of nterest then this makes UABV-UB having difficulty in choosing the players. So in this to solve the problem is used method AHP-TOPSIS. The AHP method is used for weighting which consists of making matched pair matrices, calculating matrix normalization, computing consistency test and producing krteria weight. While Topsis consists of paired normalization process of alternative data, after calculating the weighted normalization value of AHP and paired normalization process TOPSIS. The weighted normalization value will be used to find the positive and negative deal solution value as well as the distance between positive and negative deal solutions. The value is used to calculate the preference value of each alternative. Then do a ranking against the preference value. The result of system accuracy obtained from the test result is 85.7%.